KEADAAN GIZI KURANG DAN BEBERAPA ASPEK FUNGSI OTAK - Darwin Karyadi; S. Soewono; H. Tjahjadi (Persagi, 1971)
Keadaan gizi kurang dan beberapa aspek fungsi otak. (Undernutrition and some aspects of brain function). Presented at the Second National Pediatric Congress. Bandung, 1971. A group of 31 Indonesian children aged 9 to 15 years whose nutritional status had been studied over a two-year period from 1957 to 1959 were reexamined in 1969. According to their earlier classification which was made in the first examination. 10 children had been undernourished and 21 children were regarded as healthy mostly during their second and third year of life. The undernourished and healthy groups were significantly smaller than the reference Djakarta standard. Between the original undernourished and healthy groups they showed also a significant difference both in height and weight. On the basis of the clinical aspects, the healthy group remained in better physical condition. The dietary study showed low calorie and nutrient intakes particularly protein which were deficient in both groups. The parents of the children of both groups had a low income, were unskilled laborers and were illiterate. Educational placement showed that most of the children lag much behind the average for Indonesian school children. The I.Q. values were found significantly lower in the undernourished group. The large number of cases detected as abnormal, recorded as generalized or focal slow activity of the brain waves, was 64.5%. Our observations indicated that early undernutrition during the second and third year of life, also presumably earlier, resulted in retardation of both physical and intellectual developments.